Factors Affecting Trust in E-Government - Ulung Pribadi; Muhammad Iqbal; Fittia Restiane (Journal of Government and Civil Society, 2021)
This study examined perceived usefulness, information quality, and privacy and security to predict trust in e-government. This study used a survey data collection method and a random sampling technique with 100 residents who visit the local government's public services website as respondents. A Likert scale was used to create the questionnaires. SEM-PLS looked at the data to see if it was valid and reliable, as well as test hypothesis and regression. This study found that perceived usefulness, information quality, and privacy and security had a positive and significant effect on trust in e-government with p-values of 0.000, 0.001 and 0.000, respectively. The influence of the three independent variables towards the dependent variable was moderate (R-square = 0.494). Finally, the limitations and implications of these findings are examined. Studi ini menguji manfaat yang dirasakan, kualitas informasi, dan privasi dan keamanan untuk memprediksi kepercayaan pada e-government. Penelitian ini menggunakan metode pengumpulan data survei dan teknik random sampling dengan 100 orang warga yang mengunjungi website layanan publik pemerintah daerah sebagai responden. Sebuah skala Likert digunakan untuk membuat kuesioner. SEM-PLS melihat data untuk melihat apakah itu valid dan reliabel, serta menguji hipotesis dan regresi. Studi ini menemukan bahwa persepsi manfaat, kualitas informasi, dan privasi dan keamanan memiliki pengaruh positif dan signifikan terhadap kepercayaan pada e-government dengan nilai p masing-masing 0,000, 0,001 dan 0,000. Pengaruh ketiga variabel bebas terhadap variabel terikat adalah sedang (R-square = 0,494). Akhirnya, keterbatasan dan implikasi dari temuan ini diperiksa..